High‐Power, High‐Efficiency Tm:YAG and Ho:YAG Thin‐Disk Lasers (Laser Photonics Rev. 12(3)/2018). Issue 3 (25th March 2018) - Zhang, Jinwei; Schulze, Felix; Mak, Ka Fai; Pervak, Vladimir; Bauer, Dominik; Sutter, Dirk; Pronin, Oleg
Abstract : Infrared Lasers In article number1700273, Jinwei Zhang and co‐workers investigate two different gain materials—Tm:YAG and Ho:YAG—in thin‐disk configuration. Using a 72‐pass pump cavity, thin‐disk lasers with high powers and optical‐to‐optical efficiencies at 2 µm are realized, paving the way for further scaling of power towards kW‐level based on thin‐disk technology. The image was made and processed by Thorsten Naeser, Dennis Luck, and Kilian Fritsch together with the authors of this manuscript.